\[\boxed{\text{208\ (208).}\text{\ }\text{Еуроки\ -\ ДЗ\ без\ мороки}}\]
Пояснение.
Решение.
\[1)\ a^{12}\ :a^{3} = a^{12 - 3} = a^{9}\]
\[2)\ b^{6}\ :b = b^{6 - 1} = b^{5}\]
\[3)\ c^{7}\ :с^{6} = c^{7 - 6} = c^{1} = c\]
\[4)\ (a + b)^{8}\ :(a + b)^{4} =\]
\[= (a + b)^{8 - 4} = (a + b)^{4}\]
\[\boxed{\text{208.}\text{\ }\text{Еуроки\ -\ ДЗ\ без\ мороки}}\]
Пояснение.
Решение.
\[1)\ 8 \cdot (a - b + c) =\]
\[= 8a - 8b + 8c.\]
\[8a - 8b + 8c = 8a - 8b + 8c\]
\[тождество.\]
\[2) - 2 \cdot (x - 4) = - 2x - 8\]
\[- 2x + 8 = - 2x - 8\]
\[не\ тождество.\]
\[3)\ (5a - 4) - (2a - 7) =\]
\[= 3a - 11\]
\[5a - 4 - 2a + 7 = 3a - 11\]
\[3a + 3 = 3a - 11\]
\[не\ тождество.\ \]